Lactose malabsorption is a risk factor for decreased bone mineral density in pancreatic insufficient cystic fibrosis patients - Mądry, Edyta (Nature Publishing Group, 2012)
As decreased bone mineral density (BMD) is a common problem in cystic fibrosis (CF) and milk products may have pivotal dietary role affecting BMD, we aimed to assess the potential influence of adult-type hypolactasia (ATH) and lactose malabsorption (LM) on BMD in adolescent and young adult patients. In 95 CF pancreatic-insufficient patients aged 10–25 years (without liver cirrhosis, steatosis and cholestasis, diabetes mellitus, systemic glucocorticoid therapy), lumbar BMD, the nutritional status, pulmonary function, vitamin D3 concentration, calcium intake and single-nucleotide polymorphism upstream of the lactase gene were assessed. In subjects with the −13910 C/C genotype predisposing to ATH, the presence of LM was determined with the use of a hydrogen–methane breath test (BT). BMD and calcium intake were significantly lower in patients with the C/C genotype (P<0.028 and P<0.043, respectively). The abnormal BMD was stated more frequently in patients with the C/C genotype (P<0.042) and with LM (P<0.007). BMD, daily calcium intake and serum vitamin D concentration were significantly lower in LM subjects than in the other patients (P<0.037, P<0.000004 and P<0.0038, respectively). In logistic regression analysis, the relationship between examined parameters and BMD, was found to be statistically significant (P<0.001). However, only standardized body weight and LM were documented to influence BMD (P<0.025 and P<0.044, respectively). In conclusion, LM seems to be an independent risk factor for decreased BMD in CF patients.